Il pensiero cinematografico: il caso Alfred Hitchcock - Cantone, Damiano (Scenari, 2021)
The essay proposes, following the suggestions of Gilles Deleuze, a journey through the philosophy of Alfred Hitchcock. Through the analysis of the work of the English director, emerges a cinematic thought that can be, in part provocatively, brought back to the great questions of philosophy: ontology, gnoseology and ethics.